Cultures of Eschatology Volume 1: Empires and Scriptural Authorities in Medieval Christian, Islamic and Buddhist Communities Volume 2: Time, Death and Afterlife in Medieval Christian, Islamic and Buddhist Communities - Wieser, Veronika; Eltschinger, Vincent; Heiss, Johann (Cultural History of Apocalyptic Thought / Kulturgeschichte der Apokalypse, 2020)
The belief in the Last Things has an integral place in Christianity, Islam, and Buddhism. The two volumes want to explain how eschatological thought influenced and factored into the political and religious perception and self-definition of medieval communities. How did notions of an imminent end shape a community's identity, the perception of other communities and an individual's perspective towards life and the world?